The impact of variation and autonomy on psychological responses to high intensity interval training exercise - Mastrofini, G. F.; Collins, R. P.; Rosado, A. P.; Tauran, R. C.; Fleming, A. R.; Kilpatrick, M. W. (Psychology of Sport and Exercise, 2022)
Introduction High-intensity interval training (HIIT) provides notable physiological benefits and is generally well-tolerated across modalities and populations. This study investigated how exercise autonomy support impacts psychological responses to exercise.